2018
DOI: 10.1039/c8ta04020f
|View full text |Cite
|
Sign up to set email alerts
|

Dense thiol arrays for metal–organic frameworks: boiling water stability, Hg removal beyond 2 ppb and facile crosslinking

Abstract: An efficient, wide-scope synthesis of thiol-equipped MOF solids offers ever stronger binding for mercury pollutants and broader horizons for functionalization of porous materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 45 publications
0
44
0
Order By: Relevance
“…21 H 2 DMBD, as the obvious thiol-functionalized common linker terephthalate, would guarantee a high sulfur content, but is not commercially available and has to be synthesized in a complex 3-step organic synthesis under protective gas. 21,22,23 Yang et al reported two UiO-type MOFs with the organic linkers mercaptosuccinic acid (MSA) and dimercaptosuccinic acid (DMSA) forming zirconium fumarate analogs Zr-MSA and Zr-DMSA with ~12 wt% sulfur for Zr-MSA and surface areas of 513 m 2 /g and 275 m 2 /g, respectively. 13 Just recently Ding et al postsynthetically introduced rhodanine into UiO-66 (UiO-66-Rd) and amino-functionalized UiO-66-NH 2 (UiO-66-NH 2 -Rd).…”
Section: Introductionmentioning
confidence: 99%
“…21 H 2 DMBD, as the obvious thiol-functionalized common linker terephthalate, would guarantee a high sulfur content, but is not commercially available and has to be synthesized in a complex 3-step organic synthesis under protective gas. 21,22,23 Yang et al reported two UiO-type MOFs with the organic linkers mercaptosuccinic acid (MSA) and dimercaptosuccinic acid (DMSA) forming zirconium fumarate analogs Zr-MSA and Zr-DMSA with ~12 wt% sulfur for Zr-MSA and surface areas of 513 m 2 /g and 275 m 2 /g, respectively. 13 Just recently Ding et al postsynthetically introduced rhodanine into UiO-66 (UiO-66-Rd) and amino-functionalized UiO-66-NH 2 (UiO-66-NH 2 -Rd).…”
Section: Introductionmentioning
confidence: 99%
“…[3] As showni nS cheme 1, utilizingn ucleophilic substitution between benzylt hiol anda romatic halides, and AlCl 3 -promoted deprotection of the resultantb enzyl thioether,t he thiol group can be attached onto the carboxylate linker backbone-even in a dense array as in the above-mentioned H 4 OMTP linker octamercapto-tetrakis(p-benzoic acid)pyrene (H 4 OMTP;F igure 1). [3] As showni nS cheme 1, utilizingn ucleophilic substitution between benzylt hiol anda romatic halides, and AlCl 3 -promoted deprotection of the resultantb enzyl thioether,t he thiol group can be attached onto the carboxylate linker backbone-even in a dense array as in the above-mentioned H 4 OMTP linker octamercapto-tetrakis(p-benzoic acid)pyrene (H 4 OMTP;F igure 1).…”
Section: Between Then and Now: The Functional Evolutionmentioning
confidence: 99%
“…Such ap latformi sf urthere nriched by the recents ynthetic breakthrough offeringe fficient,w ide-scope protocols for accessingt hiol-equipped molecules for MOF construction. [3] As showni nS cheme 1, utilizingn ucleophilic substitution between benzylt hiol anda romatic halides, and AlCl 3 -promoted deprotection of the resultantb enzyl thioether,t he thiol group can be attached onto the carboxylate linker backbone-even in a dense array as in the above-mentioned H 4 OMTP linker octamercapto-tetrakis(p-benzoic acid)pyrene (H 4 OMTP;F igure 1). Various other thiol-equipped linker systems are being pursued, and will be duly disclosed.…”
Section: Between Then and Now: The Functional Evolutionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides metal-sulfur bond insertion, the S-S links can be easily formed by air oxidation, and the nucleophilic thiol/ thiolate were also reacted with polyfluoroarenes (Ar-F) to convert the coordination host into a covalent framework. 13,14 Versatile post-synthetic functionalization has recently been demonstrated by a porphyrin crosslinker that also enables photocatalytic hydrogen production from the 2D MOF based on Zr(IV) and H 3 TTA-6SH in Figure 3. 13 The hard-soft carboxyl-thiol design 15,16 smacks of yin yang philosophy; while the chemical execution proceeds by engaging Zr(IV) selectively with the carboxyl endpoints (by way of the hard-hard affinity), thereby avoiding interference from the thiol groups.…”
mentioning
confidence: 99%